MAGNETIC FIELD, PRESSURE AND TEMPERATURE DEPENDENT OPTICAL PROPERTIES IN A GaAs 9.0 P 1.0 QUANTUM DOT - PETER, A. JOHN; Vinolin, Ada (JOURNAL OF ADVANCES IN PHYSICS, 2014)
Simultaneous effects of magnetic field, pressure and temperature on the exciton binding energies are found in a 9.0 1.0 6.0 4.0 GaAs P / GaAs P quantum dot. Numerical calculations are carried out taking into consideration of spatial confinement effect. The cylindrical system is taken in the present problem with the strain effects. The electronic properties and the optical properties are found with the combined effects of magnetic field strength, hydrostatic pressure and temperature values. The exciton binding energies and the nonlinear optical properties are carried out taking into consideration of geometrical confinement and the external perturbations.Compact density approach is employed to obtain the nonlinear optical properties. The optical rectification coefficient is obtained with the photon energy in the presence of pressure, temperature and external magnetic field strength. Pressure and temperature dependence on nonlinear opticalÂ susceptibilities of generation of second and third order harmonics as a function of incident photon energy are brought out in the influence of magnetic field strength. The result shows that the electronic and nonlinear optical properties are significantly modified by the applications of external perturbations in a 9.0 1.0 6.0 4.0 GaAs P / GaAs P quantum dot.